Exploring opportunities for scaling of sustainable intensification interventions through farmer engagement and positive deviance approach: A case for Basona Worena, Ethiopia - Andreas, Daan; Cossu, Alessandra; Mekonnen, Kindu; Hammond, Jim; López Ridaura, Santiago; Groot, Jeroen C.J. (International Maize and Wheat Improvement Center, 2023)
In Ethiopia, much like in several other African nations, the availability of food relies significantly on a large number of smallholder farmers. These farmers, confronted with various environmental obstacles, are experiencing substantial pressure to maintain and improve food production in order to ensure a stable food supply, particularly in light of the anticipated population growth across the continent.